Explanation:
1.) (-2, 3) and (2, 9)
let (-2, 3) be (x1,y1) and (2, 9) be (x2,y2)
slope (m)=y2-y1
x2-x1
=9-3
2-(-2)
=9-3
2+2
=6
4
=3
2
2.) (0, 7) and (3, 5)
let (0,7) be (x1,y1) and (3,5) be (x2,y2)
slope (m)=y2-y1
x2-x1
=5-7
3-0
=-2
3
3.) (-2, -3) and (2, -1)
let (-2, -3) be (x1,y1) and (2, -1) be (x2,y2)
slope (m)=y2-y1
x2-x1
=-1-(-3)
2-(-3)
=1+3
2+3
=4
5
4.) (-5, -2) and (-3, 8)
let (-5,-2) be (x1,y1) and (-3,8) be (x2,y2)
slope (m)=y2-y1
x2-x1
=8-(-2)
-3-(-5)
=8+2
-3+5
=10
2
=5
5.) (-12, 20) and (-21, 29)
let (-12,20) be (x1,y1) and (-21,29) be (x2,y2)
slope (m)=y2-y1
x2-x1
=29-20
-21-(-12)
=29-20
-21+12
=9
-9
=-1
6.) (11, 8) and (-2, -3)
let (11,8) be (x1,y1) and (-2,-3) be (x2,y2)
slope (m)=y2-y1
x2-x1
=-3-11
-2-8
=-8
-10
=4
-5